Effects of white mustard (Sinapis alba) oil on growth performance, immune response, blood parameters, digestive and antioxidant enzyme activities in rainbow trout (Oncorhynchus mykiss) - Salem, Mohamed Omar Abdalla; Taştan, Yiğit; Bilen, Soner; Terzi, Ertugrul; Sönmez, Adem Yavuz (Elsevier BV, 2022)
A study was conducted to evaluate the effects of dietary supplementation of white mustard (Sinapis alba) oil (WMO) on growth performance, immune responses, digestive and antioxidant enzyme activities in juvenile rainbow trout (Oncorhynchus mykiss). For this purpose, fish (initial weight: 25.77 ± 0.13 g) were divided into four experimental groups in triplicate and fed ad libitum twice a day with diets containing WMO at 0 (control), 0.5, 1, and 1.5% of diet for 9 weeks. Three fish from each tank (n:9 per treatment) were sampled on 21st, 42nd, and 63rd days for further analyses. At the end of the feeding period, fish were challenged with Aeromonas hydrophila and Yersinia ruckeri in two separate experimental setups. Results showed that final weight, weight gain, and specific growth rate were significantly increased in all experimental groups compared to the control. Feed conversion ratio was similar among treatments. Respiratory burst and potential killing activity decreased in all experimental groups compared to the control (P < 0.05). Lysozyme and myeloperoxidase activities were elevated in all experimental groups at the end of the experiment compared to the control (P < 0.05). Cytokine gene expressions in the head kidney and intestine were elevated in all experimental groups compared to that of the control in general (P < 0.05). Hematological responses of the experimental fish groups were similar to that of the control (P > 0.05). Pepsin and trypsin levels decreased in all experimental groups (P < 0.05). In terms of antioxidant enzyme activities, significant improvement in liver superoxide dismutase, catalase, and glutathione s-transferase activities in all treatment groups were determined (P < 0.05). In addition, a significant decline in liver lipid peroxidation levels was recorded in all treated groups at all sampling times compared to the control (P < 0.05). At the end of this feeding trial, no significant differences (P > 0.05) were observed in survival against A. hydrophila among experimental groups compared to the control (P > 0.05). However, increased survival against Y. ruckeri was determined in experimental fish groups (P < 0.05). This study suggests that white mustard oil had a favorable effect on the overall health and growth of rainbow trout.
Keywords: Yersinia Infections; Immunity; Sinapis; Animal Feed; Antioxidants; Diet; Fish Diseases; Oncorhynchus mykiss; Dietary Supplements; Animals; 3. Good health